Genotype-phenotypic association of heterozygous deletion of the TBX-6 gene in patients with congenital scoliosis - Sergey E. Khalchitsky; Sergei V. Vissarionov; Polina A. Pershina; Konstantin G. Buslov; Yury A. Novosad; Marina V. Sogoyan; Marat S. Asadulaev; Marina V. Gertsyk (Гений oртопедии, 2025)
Introduction Congenital scoliosis is a multifactorial disease caused by abnormalities in vertebral development during embryogenesis. The TBX6 gene, located at locus 16p11.2, plays a key role in somitogenesis, and the heterozygous deletion is associated with the development of specific phenotypes of congenital scoliosis (TBX6-associated congenital scoliosis, TACS). Despite numerous studies on the role of TBX6 in the pathogenesis of congenital scoliosis, there is a paucity of data on the phenotypic manifestations of heterozygous 16p11.2 deletion. The objective was to identify and confirm the TACS phenotype being associated with 16p11.2 deletions in the Russian patients. Material and methods A single-center retrospective cohort study included 187 patients diagnosed with congenital scoliosis treated at the Turner National Medical Research Center for Pediatric Orthopedics and Traumatology between 2012 and 2021. Heterozygous deletion (16p11.2 region) were verified using MQRT‑PCR. The deletion group consisted of 42 patients, and the control group included 145 probands. Clinical and radiological findings were reviewed to identify localization, type and multiplicity of vertebral anomalies and associated malformations. Descriptive statistics and Pearson's correlation coefficient were used for data processing. Results Heterozygous deletion of TBX6 was detected in 22.4 % of patients. The thoracic and lumbar spine were common localizations, while involvement of the cervical spine was not identified in the deletion group. Vertebral malformations were the most common anomaly in both study groups, but their prevalence was higher among patients with TBX6 deletion (50 % vs. 43.4 %). Multiple spinal malformations were more common in the deletion group (50 % vs. 35 %). Associated internal organ defects were less common in patients with deletion (31 % vs. 43.4 %), while rib synostoses and Sprengel's disease were more common. Discussion TACS is characterized by specific manifestations including multiple vertebral malformations in the thoracic and lumbar spine, rib synostoses and Sprengel's disease, which is consistent with the scientific literature. Conclusion The findings indicate the need to include genetic testing for TBX6 deletion in the diagnostic algorithm for congenital scoliosis to facilitate early detection and a personalized approach to treatment of this cohort of patients.